Genetic testing is essential for initiating statin therapy in children with familial hypercholesterolemia: Examples from Scandinavia. (January 2021) - Svendsen, Karianne; Langslet, Gisle; Krogh, Henriette W.; Brinck, Jonas; Klausen, Ib Christian; Stenehjem, Jo S.; Holven, Kirsten B.; Bogsrud, Martin P.; Retterstøl, Kjetil
Abstract: Background and aims: In familial hypercholesterolemia (FH), statin treatment should be considered from 8 to 10 years of age, but the prevalence of statin use among children is not known. Methods: Statin use (2008–2018) among children aged 10–14 and 15–19 years was obtained from the national prescription databases in Norway, Sweden and Denmark. We assumed that all statin users in these age groups had FH, and that the estimated prevalence of FH is 1 in 250 inhabitants. Changes in prevalence rates of statin use between 2008 and 2018 by country, age and sex were estimated using the Joinpoint Regression Program version 4.8.0.1. Differences in prevalence rate ratio each year between countries were analyzed using Poisson regression. Results: Among children aged 10–14 years, there was a significant increase in statin use in Norway and Denmark between 2008 and 2018, while in Sweden an increase was only seen after 2014. Among children aged 15–19 years, an increase in statin use was only observed in Norway and Sweden between 2008 and 2018. Statin use was significantly more prevalent in Norway than in Sweden and Denmark each year, and in 2018 the proportion of children using statins was 4–5 times (10–14 years) and 3 times (15–19 years) higher in Norway compared with Sweden and Denmark. In 2018 in Norway, 19% and 35% of children aged 10–14 years and 15–19 years estimated to have FH used statins respectively; corresponding percentages in Sweden were 4.5% and 10%, and in Denmark 3% and 12%. In Norway, the increase in statin use between 2008 and 2018 roughly corresponded to the increase in children with genetically verified FH. Conclusions: Between 2008 and 2018, statin use increased in children aged 10–19 years in Norway, Sweden and Denmark, but with large differences between the countries; statin use was 3–5 times more prevalent in Norway than in Sweden and Denmark, which may be due to a more widespread use of genetic testing for FH in Norway. Graphical abstract: Image 1 Highlights : Statin use among children in Scandinavia increased between 2008 and 2018. Statin use was 3-5 times more prevalent in Norway than in Sweden and Denmark. Notably low use of statins in Denmark and Sweden. Marked increase in statin use in Sweden after 2014. Increase in statin use in Norway corresponds to increase in genetic diagnosis of familial hypercholesterolemia.